2022
DOI: 10.1002/acr.24859
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Variation at Initiation of Adalimumab and Etanercept and Clinical Outcomes in Juvenile Idiopathic Arthritis: A Childhood Arthritis and Rheumatology Research Alliance Registry Study

Abstract: Objective To determine the dose–response relationship of tumor necrosis factor (TNF) inhibition in the treatment of juvenile idiopathic arthritis (JIA). Methods Participants of the Childhood Arthritis and Rheumatology Research Alliance Registry were eligible for inclusion in the analyses if they started TNF inhibition treatment for JIA. The primary treatment response was determined 3 to 7 months after the start of treatment, based on the JIA American College of Rheumatology Pediatric criteria for improvement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In our study this dosing schedule resulted in a weight-based dosing variation median (IQR) of 0,85 (0.7 to 1.1) mg/kg body weight, with large interindividual variation of adalimumab TL even for weight corrected doses, supporting the need to include TDM to understand the correlation between dosing, systemic drug exposure, and treatment response. Although the use of body weight and BSA are relatively practical in clinical care, it is not clear what parameters of body composition correlate best with the systemic exposure and treatment response to adalimumab in children [ 32 ]. In a recent study Verstegen et al did not find meaningful differences between body weight and BSA in comparison to the alternative dosing parameters based on ideal body weight, fat free mass, and lean body weight [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study this dosing schedule resulted in a weight-based dosing variation median (IQR) of 0,85 (0.7 to 1.1) mg/kg body weight, with large interindividual variation of adalimumab TL even for weight corrected doses, supporting the need to include TDM to understand the correlation between dosing, systemic drug exposure, and treatment response. Although the use of body weight and BSA are relatively practical in clinical care, it is not clear what parameters of body composition correlate best with the systemic exposure and treatment response to adalimumab in children [ 32 ]. In a recent study Verstegen et al did not find meaningful differences between body weight and BSA in comparison to the alternative dosing parameters based on ideal body weight, fat free mass, and lean body weight [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of body weight and BSA are relatively practical in clinical care, it is not clear what parameters of body composition correlate best with the systemic exposure and treatment response to adalimumab in children [ 32 ]. In a recent study Verstegen et al did not find meaningful differences between body weight and BSA in comparison to the alternative dosing parameters based on ideal body weight, fat free mass, and lean body weight [ 32 ]. Neutralising ADA are well recognised for both infliximab and adalimumab and significantly affect drug serum concentrations and also inhibit their ability to bind with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where cDMARDs are insufficient to provide remission, bDMARDs are preferred as both mono-and combination therapy. In clinical practice, TNFi such as ETA are the first-line biologics that are the most frequently used in JIA (11,12). Data of the German registry regarding ETA use in JIA revealed that ETA is safe and effective for treatment of JIA (13).…”
Section: Discussionmentioning
confidence: 99%